Observation of Ultrahigh-Energy Cosmic Rays with the ANITA Balloon-Borne Radio Interferometer - Hoover, S; Nam, J; Gorham, PW; Grashorn, E; Allison, P; Barwick, SW; Beatty, JJ; Belov, K; Besson, DZ; Binns, WR; Chen, C; Chen, P; et al. (AMER PHYSICAL SOC, 2010)
We report the observation of 16 cosmic ray events with a mean energy of 1: 5 x 10(19) eV via radio pulses originating from the interaction of the cosmic ray air shower with the Antarctic geomagnetic field, a process known as geosynchrotron emission. We present measurements in the 300-900 MHz range, which are the first self-triggered, first ultrawide band, first far-field, and the highest energy sample of cosmic ray events collected with the radio technique. Their properties are inconsistent with current ground-based geosynchrotron models. The emission is 100% polarized in the plane perpendicular to the projected geomagnetic field. Fourteen events are seen to have a phase inversion due to reflection of the radio beam off the ice surface, and two additional events are seen directly from above the horizon. Based on a likelihood analysis, we estimate angular pointing precision of order 2 degrees for the event arrival directions.